Respuesta :

if you take the original equation, it's in y equals mx +b form so y intercept is 3 and the slope is negative 3. the inverse equation is when you put x in for y and vise versa. so x equals -3y +3. then solve for y and graph the new y =mx+b equation.

Answer:

The graph both functions in the attached figure

Step-by-step explanation:

we  have

[tex]f(x)=-3x+3[/tex]

Find the inverse of f(x)

Let

[tex]y=f(x)[/tex]

[tex]y=-3x+3[/tex]

Exchange the variables x for y and y for x

[tex]x=-3y+3[/tex]

Isolate the variable y

[tex]3y=-x+3[/tex]

[tex]y=-\frac{1}{3}x+1[/tex]

Let

[tex]f^{-1}(x)=y[/tex]

[tex]f^{-1}(x)=-\frac{1}{3}x+1[/tex] -----> inverse function

To graph the functions find the intercepts

The y-intercept is the value of y when the value of x is equal to zero

The x-intercept is the value of x when the value of y is equal to zero

For [tex]f(x)=-3x+3[/tex]

The y-intercept is the point [tex](0,3)[/tex]

The x-intercept is the point [tex](1,0)[/tex]

For [tex]f^{-1}(x)=-\frac{1}{3}x+1[/tex]

The y-intercept is the point [tex](0,1)[/tex]

The x-intercept is the point [tex](3,0)[/tex]

plot the intercepts both functions to graph the linear equations

see the attached figure

Ver imagen calculista